Mouse Models of SCN5A-Related Cardiac Arrhythmias - Charpentier, Flavien; Derangeon, Mickael; Montnach, Jérôme; Baró, Isabelle (Frontiers in Physiology, 2012)
Mutations of SCN5A gene, which encodes the α-subunit of the voltage-gated Na+ channel NaV1.5, underlie hereditary cardiac arrhythmic syndromes such as the type 3 long QT syndrome, cardiac conduction diseases, the Brugada syndrome, the sick sinus syndrome, a trial standstill, and numerous overlap syndromes. Patch-clamp studies in heterologous expression systems have provided important information to understand the genotype-phenotype relationships of these diseases. However, they could not clarify how SCN5A mutations can be responsible for such a large spectrum of diseases, for the late age of onset or the progressiveness of some of these diseases and for the overlapping syndromes. Genetically modified mice rapidly appeared as promising tools for understanding the pathophysiological mechanisms of cardiac SCN5A-related arrhythmic syndromes and several mouse models have been established. This review presents the results obtained on these models that, for most of them, recapitulate the clinical phenotypes of the patients. This includes two models knocked out for Nav1.5 β1 and β3 auxiliary subunits that are also discussed. Despite their own limitations that we point out, the mouse models still appear as powerful tools to elucidate the pathophysiological mechanisms of SCN5A-related diseases and offer the opportunity to investigate the secondary cellular consequences of SCN5A mutations such as the expression remodeling of other genes. This points out the potential role of these genes in the overall human phenotype. Finally, they constitute useful tools for addressing the role of genetic and environmental modifiers on cardiac electrical activity.